Solve using the Square Root Property (y+5)(y-7)=0

Math
(y+5)(y-7)=0
If any individual factor on the left side of the equation is equal to 0, the entire expression will be equal to 0.
y+5=0
y-7=0
Set the first factor equal to 0 and solve.
Tap for more steps…
Set the first factor equal to 0.
y+5=0
Subtract 5 from both sides of the equation.
y=-5
y=-5
Set the next factor equal to 0 and solve.
Tap for more steps…
Set the next factor equal to 0.
y-7=0
Add 7 to both sides of the equation.
y=7
y=7
The final solution is all the values that make (y+5)(y-7)=0 true.
y=-5,7
Solve using the Square Root Property (y+5)(y-7)=0

Download our
App from the store

Create a High Performed UI/UX Design from a Silicon Valley.

Scroll to top